IMPLEMENTATION OF THE KKN-T PROGRAM IN COMMUNITY EMPOWERMENT THROUGH EDUCATION, HEALTH, ENVIRONMENT, AND LEGAL AWARENESS EDUCATION IN SAMPORA VILLAGE - Nurul Senja; Adit Hartadi; Aliya Dwi Putri; Agia Amala Yudha; Azhah Nurlita Maulin; Alif Khunaefi; Gisca Livia Laury; Burhanuddin Abdullah; Erika Nur Oktavia; Cahya Seftian Ramadhan; Gina Yuliyanti; Farhan Haban Nugraha; Lutfiyah Lutfiyah; Gallih Prakoso Zatti; Putri Ayu Lennas; Ilham Shofil Fuadi; Rezka Dwi Jesrizal; Winata Yudistira; Thesa Nurshela; Yholan Chernando (Jurnal Abdisci, 2026)
Background. The Thematic Real Work Lecture (KKN-T) is a form of community service that aims to increase community capacity and awareness through various empowerment programs. This activity was carried out in Sampora Village, focusing on education, health, the environment, and legal awareness. Method. The method used is a qualitative, participatory approach through the stages of observation, program planning, activity implementation, and evaluation. Results. The results of the activity show an increase in knowledge and community participation. In the field of education, teaching activities and anti-bullying socialization were carried out for elementary school students. In the health sector, education on Clean and Healthy Living Behavior (PHBS) and genital hygiene education for elementary school students was carried out, free health checks, health education on the dangers of smoking in adolescents for junior high school students. In the field of engineering, an administrative map of Sampora Village was made. In addition, legal counseling on juvenile delinquency for junior high school students, socialization of increasing legal awareness for village communities to increase legal awareness through seminars on the impact of serial marriage on families. Implementation. This program makes a positive contribution in encouraging community participation and supporting sustainable village development.